Applications of Artificial Intelligence in Veterinary Medicine: A Review - Divya Sri, B.; K.Benarji; Palli Avinash; G.Saikumar; M.G.Jayathangaraj; R.K.Swain (The Indian Veterinary Journal, 2026)
This paper explores the transformative applications of Artificial Intelligence (AI) in veterinary medicine, including diagnostic enhancements, personalised treatment, and animal welfare monitoring. Key areas included using AI in image interpretation, automated pathology, wearable health-monitoring devices, and outbreak prediction. AI’s integration in education is also discussed, highlighting virtual reality for skill development. Challenges, such as data security, bias, and ethical implications, are addressed to emphasize responsible AI deployment, besides discussing the AI’s potential to improve diagnostic accuracy, streamline treatments, and advance animal health, paving the way for future innovations in veterinary care.